Design and validation of a novel new instrument for measuring the effect of moral intensity on accountants' propensity to manage earnings - Ng, Jeanette; White, Greg; Lee, Alina; Moneta, Andreas (Springer Netherlands, 2009)
The goal of this study was to construct a valid new instrument to measure the effect of moral intensity on managers' propensity to manage earnings. More specifically, this study is a pilot study of the impact of moral intensity on financial accountants' propensity to manage earnings. The instrument, once validated, will be used in a full-study of managers in the hotel industry. Different ethical scenarios were presented to respondents in the survey; each ethical scenario was designed in both high or low moral intensity form, to reflect the importance of the moral dilemma at hand. The results were analysed by factor analysis. The findings of this study have positively validated the instrument, with three of the five moral intensity components identified as having appropriate eigenvalues. This indicates that they have a significant influence in the study. The first factor captures the social consensus dimension and one scenario of the proximity dimension. The second factor indicates an interaction between thetemporal immediacy and the magnitude of consequences dimension. The third dimension is probability of effect and one scenario of the proximity dimension. In addition, t-tests indicated that the manipulation of high and low conditions within each scenario were also successful. One limitation of the study might be the use of undergraduate accounting students as manager proxies, although prior evidence suggests use of accounting students as proxies is a valid approach in this type of study. This is a highly novelproject as most prior studies have focussed on moralintensity and the general ethical decision-making process.